Buddhist Economic in Thailand - Sridokbua , Phra Ketsamrit Thitasilo; Pangthipampai, Parinun (Journal of Dhamma for Life, 2023)
This academic article aims to study Buddhist economics in Thailand. "Buddhist economy" to expand the meaning so that many people and some of you have a deeper understanding and can think or think about what I’m communicating to you. Knowing how to work, knowing the duties that one should be supposed to and having to do for oneself, for the family, and society, and understanding oneself. Understand society, understand one’s duties, and other duties, understand the rules, and understand what roles should be and how we should behave. What should I do? In each of the roles that were being played at that time, for example, a white person was a woman. Is the child of the father’s mother in life? When a husband grows up, she is a wife, when she has children, she is a mother, when a son has children, she is a grandmother, when a daughter has children, she is a grandmother, etc. Everything is a rule that is assumed to be used as a definition to use to communicate and understand each other and in order to do various activities as needed. There is a standard, there is a consensus to define a respectful contract, known to be used successively, for example, used to communicate "what is this?”